2018
DOI: 10.1103/physrevb.97.165416
|View full text |Cite
|
Sign up to set email alerts
|

Mapping momentum-dependent electron-phonon coupling and nonequilibrium phonon dynamics with ultrafast electron diffuse scattering

Abstract: We show that ultrafast electron diffuse (inelastic) scattering provides a detailed, momentum-resolved view of electron-phonon and phonon-phonon coupling across the entire Brillouin zone. Ultrafast time-resolution and scattering selection rules can distinguish between phonon branches without energyresolution.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 41 publications
5
98
3
1
Order By: Relevance
“…Transient electron diffuse intensity has been used elsewhere[20][21][22][23] as an approximation to the population dynamics of particular modes. However, one can extract the transient wavevector-dependent phonon population dynamics {∆n j,k (t)} by combining the measurements of ∆I(q, t) with the calculations of one-phonon structure factors and associated quantities presented above.For many materials (including graphite), the temperature dependence (and hence time de-q, t 0 )| 2 [a.u.]…”
mentioning
confidence: 99%
“…Transient electron diffuse intensity has been used elsewhere[20][21][22][23] as an approximation to the population dynamics of particular modes. However, one can extract the transient wavevector-dependent phonon population dynamics {∆n j,k (t)} by combining the measurements of ∆I(q, t) with the calculations of one-phonon structure factors and associated quantities presented above.For many materials (including graphite), the temperature dependence (and hence time de-q, t 0 )| 2 [a.u.]…”
mentioning
confidence: 99%
“…Scattering patterns exhibiting n -fold rotational symmetry can be transformed to yield a higher signal-to-noise ratio. This approach has recently been used to extract small ultrafast diffuse scattering signals from graphite [ 26 ]. An example of such symmetrization is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Combining the spatial resolution of electron microscopy and femtosecond time-resolution, this laboratory-scale technique has shed light on a broad spectrum of phenomena, from photoinduced structural phase transitions in inorganic [ 21 , 32 ] and organic materials [ 8 ], to coherent nuclear motion in dilute molecular gas [ 36 ]. Beyond probing structure through elastic interactions, UES has provided a direct observation of electron–phonon couplings and phonon relaxation pathways in layered materials [ 26 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…which range from 1 to 115 ps. 23 The substrate phonons most efficient in transferring momentum to the NCs are flexural ZA phonons 2 with a wavelength l \ 2.6 nm (2.6 nm is the characteristic dimension of the Au 923 NC binding facet). It is expected that the transfer of linear momentum will be accompanied by transfer of angular momentum, since the ZA phonons propagate parallel to the NC-graphene interface, thereby exerting torque on the NC upon scattering.…”
Section: Discussionmentioning
confidence: 99%
“…In graphene, excitation and thermalization of acoustic waves (transverse and longitudinal phonons termed TA and LA, respectively) occurs within the first 100 ps. 22,23 The timescale for generation of flexural ZA phonons (out of graphene plane atomic vibrations) and dynamic rippling is in the order of 50 ps. 24 Detailed theoretical considerations by Panizon et al 2 have shown that transfer of momentum from graphene to adsorbed Au NCs is carried out by flexural ZA phonons or by and the (220) peaks (red and blue data-points, respectively) and biexponential fittings (solid lines).…”
Section: Femtosecond Electron Diffractionmentioning
confidence: 99%